GAMBARAN STRES GURU BIMBINGAN DAN KONSELING DALAM MENGHADAPI PESERTA DIDIK AUTISTIK DI SMK NEGERI 4 PADANG - -, Japrianto - (Bimbingan dan Konseling, 2014)
This research was caused by obstruction of guidance and counselling teacher in facing the autisticstudents that ensue the disturbance of physique and psychological health such as feel fatigued, irritationof skin, asthma, the illness of heart, migraine, anxiety, restless, wrathfulness, hostility, can not think welland mental depression. This research focused on to know the stress description of guidance andcounselling teacher in facing the autistic students which is seen from physique and psychological aspectof guidance and counselling teacher in SMK N 4 Padanng. This research was qualitative research withdescriptive approach which describe the indication, fact and reality that comes as in the field about stressdescription of guidance and counselling teacher in facing the autistic students. The informant of thisresearch was three guidance and counselling teachers, two other subject teachers and four autisticstudents. The instrument of this research used interview and observation. The techniques that are used inprocessing data were reduction data, presenting data and making conclusion. The result of this researchwas: (a) stress descriptions of guidance and counselling teacher from physic aspect are the guidance andcounselling teacher often feel fatigued when the students difficult to manage, shocked when the teacherhear autistic students scream and angry uncontrolled, also often feel dizzy when the autistic students didnot want to learn. (b) Stress descriptions of guidance and counselling teacher from psychological aspectare the guidance and counselling teacher often feel anxious and restless when the autistic students hit theirfriends.